Bilateral Granulomatous Iridocyclitis Associated with Early-Onset Juvenile Psoriatic Arthritis - Christian Nieves-Ríos; Guillermo A. Requejo Figueroa; Sofía C. Ayala Rodríguez; Alejandra Santiago-Díaz; Eduardo J. Rodriguez-Garcia; Alejandro L. Perez; Erick Rivera-Grana; Adriana C. Figueroa-Díaz; Rafael Martín-García; Armando L. Oliver (Case Reports in Ophthalmological Medicine)
Purpose. The purpose of this study is to report on a case of bilateral granulomatous iridocyclitis in a patient with early-onset juvenile psoriatic arthritis (JPsA). Methods. The method used is an observational case report. Observations. A 3-year-old Hispanic girl was sent to our uveitis service for further evaluation of her granulomatous uveitis. The initial ophthalmologic examination revealed bilateral band keratopathy, large mutton-fat keratic precipitates, multiple posterior synechiae, and 4+ anterior chamber cells. The physical exam was notable for left knee edema and right axillary rash. Laboratory testing was remarkable for an erythrocyte sedimentation rate of 80 mm/h, positive antinuclear antibodies (1 : 1, 280), and negative human leukocyte antigen B27. A cutaneous biopsy was obtained, which confirmed the diagnosis of a psoriatic rash. Treatment with oral prednisolone and topical prednisolone acetate with atropine sulfate resulted in the complete resolution of the uveitis. Conclusion and Importance. Bilateral granulomatous iridocyclitis may be a rare presentation of ocular involvement in patients with early-onset JPsA.